Security of the Energy Supply in Turkey: Prospects, Challenges and Opportunities - Esen, Ömer (International Journal of Energy Economics and Policy, 2016)
In today's world, energy is one of the most important inputs for a multitude of industries and production branches. Access to uninterrupted, adequate, reliable, cheap, stable and sustainable energy has become essential to the basic functioning of modern societies. Ensuring energy security is of critical importance in terms of economic stability and sustainable growth. Interruptions in the energy supply can cause serious economic and social losses. Lack of energy security discourages investors by threatening production and increasing costs. The aim of this study is to identify the primary risks concerning the security of the energy supply in Turkey and to propose solutions. The study discusses the current state of energy security in Turkey, which is substantially dependent on foreign supply to meet its energy needs. The study also examines the importance of the advantages and opportunities offered to Turkey by both domestic and renewable resources, which are not being fully utilized, despite their high potential, and Turkey's potential to become an energy transit hub in terms of energy security. Keywords: Turkey; energy security; energy diversity; transit route JEL Classifications: Q41; Q43; Q48